Simulation of transient ultrasonic wave propagation in fluid-loaded heterogeneous cortical bone - Nguyen, Vu Hieu; Naili, Salah (Vietnam Journal of Mechanics, 2011)
This work deals with the ultrasonic wave propagation in the cortical layer of long bones which is known as being a functionally-graded anisotropic material coupled with fluids. The motivation arises from mechanical modeling of the ultrasound axial transmission technique in vivo for cortical long bone which is known as being a functionally-graded anisotropic material. The proposed method is based on a combined Laplace-Fourier transform which substitutes a problem defined by partial differential equations into a system of differential equations established in the frequency-wavenumber domain. In the spectral domain, as radiation conditions may be exactly introduced in the infinite fluid half-spaces, only the heterogeneous solid layer needs to be analyzed using finite element method. Several numerical tests are presented showing very good performance of the proposed approach.